Development of a pre‐ and postoperative physical activity promotion program integrated in the electronic health system of patients with bladder cancer (The POPEYE study): An intervention mapping approach. (17th November 2020) - Rammant, Elke; Deforche, Benedicte; Van Hecke, Ann; Verhaeghe, Sofie; Van Ruymbeke, Barbara; Bultijnck, Renée; Van Hemelrijck, Mieke; Fox, Louis; Pieters, Ronny; Decaestecker, Karel; Fonteyne, Valérie
Abstract: Introduction: Uptake of sufficient physical activity before and after radical cystectomy is important to improve physical and psychosocial outcomes in bladder cancer (BC) patients. Methods: In this paper, we describe the development of an evidence‐based and theory‐informed intervention, guided by the steps of the Intervention Mapping approach, to promote physical activity before and after radical cystectomy in patients with BC. Results: The intervention is a home‐based physical activity program. The preoperative timeframe of the intervention is 4 or 12 weeks, depending on administration of neoadjuvant chemotherapy. Postoperatively, the intervention will last for 12 weeks. The intervention consists of a digital oncological platform (DOP), several consultations with healthcare professionals, personal booklet and follow‐up phone calls. DOP includes information, diaries, visual representation of progress, mailbox, videos of peers and treating physician explaining the benefits of physical activity, photo material of exercises and a walking program with an activity tracker. Individual goals will be set and will be self‐monitored by the patient through DOP. Patients will receive alerts and regular feedback. Conclusions: Intervention Mapping ensures transparency of all intervention components and offers a useful approach for the development of behaviour change interventions for cancer patients and for translation of theories into practice.